Ga2O3 metal–insulator-semiconductor solar-blind photodiodes with plasmon-enhanced responsivity and suppressed internal photoemission. (16th March 2023) - Zhang, Chong-De; Ren, Fang-Fang; Yu, Mingbin; Zhang, Baoshan; Gu, Shulin; Zhang, Rong; Zheng, Youdou; Ye, Jiandong
Abstract: Metal-semiconductor-metal (MSM) architectures are popular for achieving high-responsivity Ga2 O3 solar-blind photodetectors (SBPDs), however, the hot-electron-induced internal photoemission (IPE) effect restricts their detecting performance. Herein, we demonstrate the rational design of an Al/Al2 O3 /Ga2 O3 metal–insulator-semiconductor (MIS) SBPD that has merits of enhanced responsivity, suppressed sub-gap response and ultralow dark current based on the simulation results obtained using Lumerical software. For the cylindrical patterned detectors with Al/Al2 O3 /Ga2 O3 MIS structures, the optimized dimensions of Al electrodes with a conformed ultra-thin (2 nm) Al2 O3 layer support the surface plasmon polariton resonances at 250 nm, thus improving the photoresponsivity to 74 mA W −1 . Furthermore, the sandwiched Al2 O3 layer lifts the barrier for hot electrons in electrodes, which significantly suppresses the IPE-induced sub-gap photoresponse by more than 10 5 in magnitude with respect to the Al/Ga2 O3 MSM counterpart. Optical and electrical field distributions are overlapped in cylindrically patterned MIS detectors, simultaneously improving the excitation and collection efficiencies of excess carriers and resulting in the 10 3 -boosted rejection ratio.